2020
DOI: 10.1002/pssa.202000483
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐Infrared Photodetector Based on Selenium‐Doped Black Phosphorus

Abstract: Black phosphorus (BP), a new elemental 2D material, is a suitable candidate for broadband photodetection from the visible to the infrared (IR) range of the spectrum because of its tunable bandgap and high carrier mobility. Herein, the electrical and optical properties of pristine and Se‐doped BP have been investigated, using the density functional theory (DFT) method. The results show that the Se‐doped BP has an indirect bandgap of 0.4 eV which is smaller than that of the pristine monolayer BP. Moreover, the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Moreover, the photodetector had effective photoresponse in the kilohertz frequency range due to the carrier dynamics of BP with a moderate bandgap. In addition, Jalaei et al reported a Se-doped BP photodetector with high responsivity ranging from 3 to 5 µm [143]. Se-doped BP showed smaller bandgap as well as higher absorption coefficient in the mid-infrared region compared to the pristine BP.…”
Section: Black Phosphorusmentioning
confidence: 99%
“…Moreover, the photodetector had effective photoresponse in the kilohertz frequency range due to the carrier dynamics of BP with a moderate bandgap. In addition, Jalaei et al reported a Se-doped BP photodetector with high responsivity ranging from 3 to 5 µm [143]. Se-doped BP showed smaller bandgap as well as higher absorption coefficient in the mid-infrared region compared to the pristine BP.…”
Section: Black Phosphorusmentioning
confidence: 99%